2015
DOI: 10.1007/s00167-015-3679-4
|View full text |Cite
|
Sign up to set email alerts
|

Is quality of life following hip arthroscopy in patients with chondrolabral pathology associated with impairments in hip strength or range of motion?

Abstract: Cross-sectional study, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…Emara et al 25 suggest modifications to those activities of daily living that may be exacerbated by FAI and maintaining function within ‘safe range of movement’ as a means of improving function and reducing symptoms. Other modifiable impairments such as greater hip flexion range and adduction strength have been associated with higher quality-of-life patient-reported outcome scores in patients with chondrolabral pathology 12–24 months posthip arthroscopy 11. Programmes targeted at improving these specific impairments as well as other strength and functional movement patterns around the hip may help improve functional outcomes for those with symptomatic FAI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emara et al 25 suggest modifications to those activities of daily living that may be exacerbated by FAI and maintaining function within ‘safe range of movement’ as a means of improving function and reducing symptoms. Other modifiable impairments such as greater hip flexion range and adduction strength have been associated with higher quality-of-life patient-reported outcome scores in patients with chondrolabral pathology 12–24 months posthip arthroscopy 11. Programmes targeted at improving these specific impairments as well as other strength and functional movement patterns around the hip may help improve functional outcomes for those with symptomatic FAI.…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic FAI can have a significant impact on pain, function and quality of life outcomes in the young and middle aged4 11 that may ultimately reduce their capacity to lead active and productive lives. Identifying potentially modifiable impairments in patients with symptomatic FAI is important.…”
Section: Introductionmentioning
confidence: 99%
“…The average hip flexion ROM (Figure ) in the severe subgroup prior to arthroscopy was 102°. Kemp et al () previously reported the associations between decreased quality of life and decreased hip flexion ROM in a post hip arthroscopy group were strongest in those with less than 100° of ROM. This provides clinicians with a useful measure when determining the likely severity of symptoms and functional limitations in patients both before and after hip arthroscopy.…”
Section: Discussionmentioning
confidence: 95%
“…Hip chondral lesions and acetabular labral tears are well‐recognized contributors to hip and groin pain in individuals undergoing hip arthroscopy (Kemp et al, ; Kemp, Makdissi, Schache, Pritchard et al, ). These findings are often associated with femoroacetabular impingement syndrome (FAI syndrome; Griffin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hip and groin pain is common in the community [216] and in sporting populations [221]. Hip chondral lesions and acetabular labral tears are well recognized contributors to hip and groin pain in individuals undergoing hip arthroscopy [116,117]. These findings are often associated with femoroacetabular impingement syndrome (FAIS), which is a motion-related clinical disorder of the hip with a triad of symptoms, clinical signs, and imaging findings often affecting young active adults [76].…”
Section: Hip Intra-articular Pathologymentioning
confidence: 99%